Analisis Dampak Aktivitas Masyarakat Terhadap Kualitas Air di Obyek Wisata Pantai Sri Mersing Kecamatan Pantai Cermin Kabupaten Serdang Bedagai - Eka Tri Rahayu; Pindi Patana; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Coastal waters nowadays is like a final shelter of kinds waste generated by humanactivity from agriculture, household, waste disposal of fish landings etc. If theyhas exceeded the carrying capacity, the water quality will decrease, and beingpolluted physically, chemically, microbiological and affect the beauty and comfortof visitors in the tour activities. Research was conducted at Sri Mersing Beach,District Pantai Cermin, Serdang Bedagai in August-November 2014 by analyzingthe water quality of the River Sei Baungan and Sri Mersing Beach. It comparedwith the water quality standard based Kep-51/MENLH/2004 for marine tourism,assessed the quality of the coastal environment, the potential for the developmentof coastal tourism, and to got the perception of tourists to the beauty and comfortof the destination. The results showed that there were several water qualityparameters that were not in accordance with the water quality standards fortourism activities with the existence of rubbish, turbidity and Colifaecal.Assessment of environmental quality of coastal area of research is categorizedextremely suited for coastal tourism and potentially to be used as a destination.Keywords: water quality, coastal quality, Sei Baungan, Sri Mersing, tourism potential.